The transgression of the maternal voice in the poetry of Gabriela Mistral (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
A new language begins to take shape that reflects the surrounding reality, a language of opposition and resistance. Gabriela Mistral was aware of the role of women and the artist in her time. The discourses that emerge from the Latin American literary magazines of the 1920s and subsequent years situate the efforts of the writers of the new generation within an imaginary political order. In the writer's position, it is not one of real power but of complicity or resistance. From that place, he resists or identifies with the system of power. The speeches of the time are pronounced against external power, enunciating an apparent freedom as if escaping the tyrannical strategy of power.